How does the digital economy promote green technology innovation by manufacturing enterprises? Evidence from China - Ning, Jing; Yin, Qiaorong; Yan, An (Frontiers in Environmental Science, 2022)
With the rapid development of the digital economy and the increasingly severe environmental issues, the role of digital economy in green innovation is gradually attracting more attention. However, only a limited amount of research analyzes the impact of digital economy on green innovation. Therefore, based on the matched data at the cities and manufacturing enterprises levels during 2011-2018 in China, this paper attempts to introduce digital economy (more specifically Internet and digital finance), resource allocation and green technology innovation within a unified scheme. We confirm that digital economy can significantly promote green technology innovation of manufacturing enterprises, but digital finance is more prominent. Resource allocation efficiency plays a partial mediating role between digital economy and green technology innovation. Furthermore, with the consideration of heterogeneity in enterprise ownership and industrial pollution, digital economy plays a more positive effect on green technology innovation for state-owned enterprises (SOEs) and high pollution industries. As for the heterogeneity of region, Internet significantly contributes to green technology innovation in regions with different developing levels. Especially in the eastern region of China, the role of digital finance on green technology innovation is more significant. In view of these, this study provides important implications of strengthening the integration of digital economy and green transformation, emphasizing the rationality of resource allocation, and formulating policies for different enterprises.